Periodic Behavior of Lanthanide Coordination within Reverse Micelles. Issue 8 (7th January 2013) - Ellis, Ross J.; Meridiano, Yannick; Chiarizia, Renato; Berthon, Laurence; Muller, Julie; Couston, Laurent; Antonio, Mark R.
Abstract Trends in lanthanide(III) (LnIII) coordination were investigated within nanoconfined solvation environments. LnIII ions were incorporated into the cores of reverse micelles (RMs) formed with malonamide amphiphiles in n‐heptane by contact with aqueous phases containing nitrate and LnIII; both insert into pre‐organized RM units built up of DMDOHEMA (N, N′‐dimethyl‐N, N′‐dioctylhexylethoxymalonamide) that are either relatively large and hydrated or small and dry, depending on whether the organic phase is acidic or neutral, respectively. Structural aspects of the LnIII complex formation and the RM morphology were obtained by use of XAS (X‐ray absorption spectroscopy) and SAXS (small‐angle X‐ray scattering). The LnIII coordination environments were determined through use of L3‐edge XANES (X‐ray absorption near edge structure) and EXAFS (extended X‐ray absorption fine structure), which provide metrical insights into the chemistry across the period. Hydration numbers for the Eu species were measured using TRLIFS (time‐resolved laser‐induced fluorescence spectroscopy). The picture that emerges from a system‐wide perspective of the LnO interatomic distances and number of coordinating oxygen atoms for the extracted complexes of LnIII in the first half of the series (i.e., Nd, Eu) is that they are different from those in the second half of the series (i.e., Tb, Yb): the number of coordinating oxygen atoms decrease from 9 O for early lanthanides to 8 O for the late ones—a trend that is consistent with the effect of the lanthanide contraction. The environment within the RM, altered by either the presence or absence of acid, also had a pronounced influence on the nitrate coordination mode; for example, the larger, more hydrated, acidic RM core favors monodentate coordination, whereas the small, dry, neutral core favors bidentate coordination to LnIII. These findings show that the coordination chemistry of lanthanides within nanoconfined environments is neither equivalent to the solid nor bulk solution behaviors. Herein we address atomic‐ and mesoscale phenomena in the under‐explored field of lanthanide coordination and periodic behavior within RMs, providing a consilience of fundamental insights into the chemistry of growing importance in technologies as diverse as nanosynthesis and separations science.